Beyond the Counter: Exploring Return Management as a Social Practice in Large-Scale Retail - Fatharani,Afina; Htet,Swan (2025)
This thesis explores how return policies are enacted and adapted in large-scale retail practice through the everyday work of employees. Using Social Practice Theory (SPT) as a theoretical framework, the study investigates how large-scale retail’s 365-day return policy is interpreted, negotiated, and performed by employees across diﬀerent regional and organizational settings. While return management is often understood in terms of logistics and consumer behavior, this thesis focuses on the operational and emotional realities faced by employees, highlighting how returns work involves situated judgment, cross-functional collaboration, and emotional labor. The research draws on 14 semi-structured interviews with large-scale retail employees from eight countries, combined with non-participant observations conducted in Sweden and Denmark. Findings show that return practices are shaped not only by formal policy and digital systems but also by regional customer norms, informal learning, and frontline innovation. Employees do not passively implement policy but actively make it work, adapting routines, improvising with tools, and navigating tensions between customer satisfaction and business sustainability. By examining returns as a socially and materially embedded practice, the thesis provides new insights into how service policies are sustained and reconfigured in daily work. It contributes to both service management and organizational studies by emphasizing the interpretive and emotional dimensions of returns work and by showing how employee agency, competence, and collaboration drive everyday service innovation.
Keywords: product returns; Social Practice Theory; emotional labor; large-scale retail; service work; return policy; organizational routines; employee competence; retail innovation